Impact Of Social Networking Sites On Secondary Students For Achieving Sustainable Education - Siddiqui, Mehwish; Khan Lodi, Adnan (International Journal of Psychosocial Rehabilitation, 2020)
The word Sustainable Development Goal comprises seventeen global goals that were formulated by the United Nations in order to transform the world into a more sustainable future, which will, in the end, lead to a more prosperous, happy, and healthy life and shape the future into a better one. Today, the world is facing serious issues and challenges such as the natural resources declining day by day, irregularity in climate change, increasing pollution, the hunger index of our nation rising with each passing day, and the quality of education having to be improved and updated according to the needs of the society as well as global needs. When we take a view of our environment, our ecosystem has now been totally disturbed. People are so busy upgrading themselves and adopting new science and technologies that we are forgetting that we are playing with our mother earth and disturbing the balance of the human cycle. While the world has been moving towards deterioration, it is today necessary to pay attention to these issues, and major steps should be taken to eradicate these issues. The paper will further discuss the importance of social media and how it is accomplishing the major goals of sustainable development in education. The goals can be fulfilled with the help of using social media, as it is today’s most powerful tool to achieve something in order to bring a change in the world. People now are totally dependent and feel friendly using these technologies; the government is also running so many schemes so that every student gets all the necessary resources to attain high-quality education whether they are living in the city or remote areas. Thus, social media is a very good medium nowadays for spreading awareness and necessary information to everyone within a few seconds. Thus, social networking sites are important tools that help in fulfilling sustainable development and spreading more knowledge regarding these goals.